Electronic Media Taxpayer Education and Monthly Rental Income Tax Adherence Among Residential Landlords in Bungoma County, Kenya (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Monthly rental income tax compliance remains a practical concern in Kenya because weak compliance constrains domestic revenue mobilization and shifts the burden onto compliant taxpayers. This article examined the influence of electronic media taxpayer education on monthly rental income tax adherence among residential landlords in Bungoma County, Kenya. The article was guided by Fiscal Exchange Theory and Social Influence Theory, with tax awareness, organizational trustworthiness, and digital competence serving as explanatory mechanisms to interpret the relationship. The research adopted a descriptive research design. From the target population of 153,653 residential rental property owners, a sample of 399 landlords was obtained using Yamane's formula and stratified random sampling. Structured questionnaires generated 326 usable responses. (Urban Planning Challenges and Community Resilience: An Empirical Assessment of Disaster Vulnerabilities in Bungoma Municipality, 2023, pp. 100-110) Data were examined using descriptive statistics, reliability analysis, Pearson correlation, and simple linear regression. Results showed that electronic media taxpayer education had a strong, positive, and statistically significant relationship with monthly rental income tax adherence, r = .838, p < .001. Regression results further indicated that electronic media taxpayer education explained 70.2% of the variation in adherence (R² = .702), F (1, 324) = 765.047, p < .001. The article concluded that radio, television, SMS alerts, email alerts, social media, and the KRA website can strengthen adherence when messages are timely, credible, and easy to act on. The article recommends segmented electronic taxpayer education that combines deadline-based reminders, radio explanations, verified social media updates, and simplified online guidance.